2010
DOI: 10.14704/nq.2010.8.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Theory of Everything Part III: Introduction of Consciousness in Loop Quantum Gravity and String Theory and Unification of Experiences with Fundamental Forces

Abstract: Theory of everything must include consciousness. In this article, we focus on introducing the subjective experience (SE) aspect of consciousness in modern quantum physics, namely, loop quantum gravity (LQG) and string theory by using the methodology of examining invariance of these theories under the PE-SE transformations, where PEs (proto-experiences) are precursors of SEs. In our dualaspect-dual-mode PE-SE framework, (i) each of strings, loops, elementary particles, inert matter, or neural-networks has physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Under the PE-SE transformations, (a) in Part I (Vimal, 2010c), we found that classical physics is invariant, and (b) in Part III (Vimal, 2010d), it will be shown that modern quantum physics is invariant.…”
Section: Invariance Of Classical Physics and Modern Quantum Physics Umentioning
confidence: 74%
See 2 more Smart Citations
“…Under the PE-SE transformations, (a) in Part I (Vimal, 2010c), we found that classical physics is invariant, and (b) in Part III (Vimal, 2010d), it will be shown that modern quantum physics is invariant.…”
Section: Invariance Of Classical Physics and Modern Quantum Physics Umentioning
confidence: 74%
“…In Part III (Vimal, 2010d), the SE aspect of consciousness will be introduced in modern quantum physics that includes loop quantum gravity (LQG) and string theory of quantum physics using the same methodology of examining their invariance. It will be shown that LQG and string theory are also invariant under the PE-SE transformations.…”
Section: Abbreviations and Symbols Listmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted in the Introduction, part B, interpreting [168], [169] quantum theory, particularly in light of future quantum computing developments, may be a lengthy and complicated process because it may require a unified and acceptably empirical cosmology. Arguably, a final interpretation of quantum physics is a work in progress and is possibly dependent on quantum-computing results themselves as well as a cosmology that reciprocally integrates classical, relativity, and quantum theories into a unified Theory of Everything (ToE) [115], [170]- [175]. Pending development of this integration, with or without convincing metaphysics, an apparent circular, conceptual interdependence remains unresolved to the extent that such a ToE itself requires a new "emergent quantum" interpretation [170], [176] that provides for measurable integrated causation [177], or not, among its subsidiary, reconfigured elements.…”
Section: ) Sagi: Physics Metaphysics Consciousness Panpsychism Amentioning
confidence: 99%
“…Fundamental entities, such as strings or elementary particles, may have material and mental aspects, such as mass, charge, or spin. To combine consciousness with TOE, classical physics, quantum physics, loop quantum gravity, and string theory introduced these aspects [ 271 ].…”
Section: Introductionmentioning
confidence: 99%